EFFECT OF SOAKING TREATMENT AND FLOUR TYPE ON THE QUALITY AND SENSORY ATTRIBUTES SHALLOTS - Anggarkasih, Made Gayatri; Nurlela, Nurlela; Tunggadewi, Andini Tribuana; Merdekawati, Eka (IPB University, 2025)
Shallots are a key ingredient in Indonesian cuisine, both traditional and modern, and offer added value when processed into fried shallots. This study aimed to determine the best treatment combination regarding yield, chemical quality (moisture and fat content), and sensory acceptance (color, taste, aroma, appearance). The shallots were sourced from local markets in Bogor and processed in the Vocational School Laboratory at IPB University using a Completely Randomized Design (RAL) with six treatment combinations, involving soaking and flour coating variations. Data were analyzed using ANOVA followed by Duncan's test at a 95% significance level. Results showed that soaking and flour type significantly affected yield, chemical quality (moisture and fat content), and sensory quality. The treatment involving soaking and wheat flour produced the crispiest texture with the lowest moisture content (4.01%) and was the most preferred by panelists.